Right to equality and justice under international Islamic instruments and the Shari'ah: An evaluation - Ab Aziz, Shamrahayu; Sambo, A.O. (INSI Publications, 2012)
One of the problems confronting humanity today is the violation of peoples’ right to equality and justice. Inequality and injustice appear to be the order of the day in many countries of the world. It is not limited to underdeveloped or developing nations. Developed nations also have their share. However, much talk on violation the right to equality and justice appears to be focused on Muslim countries. Yet, the Shari‛ah provides for lofty principles of justice and equality. Also, international Islamic instruments emphasise on the peoples’ right to equality and justice. As a result, many people in these countries clamour for their rights to be treated equally, fairly and justly. These terms are though often misused. This paper therefore analyses the right to equality and justice from perspectives of international Islamic instruments and the Shari‛ah. It finds that the Shari‛ah provides for many ways to promote the peoples’ right to equality and justice. In doing this, verses of the Qur’an, Sunnah of the Prophet (s.a.w.) and opinions of Muslim scholars are used to enrich the legal analysis.